Geochemistry of sediment and heavy metals on the major estuarine mangrove forest of Terengganu, Malaysia - Ong Meng Chuan (IInstitut Oseanografi, 2011)
A geochemistry and sedimentology study had been conducted at major estuarine mangrove forest (Kemaman-Chukai, Kerteh, Palca, Dungun, Marang and Setiu) of Terengganu region. A total of seven transects with 100 sampling points were setup inside the mangrove forest. Two sampling were carried out to present the dry and wet season. The dry and wet season period sampling was represented by 10th to 20lh May 2004 and 2nd to 8th January 2005, respectively. The heavy metal concentration, sediment characteristic, organic carbon content and sedimentation rate had been determined in this study.